Optimal Release of Information By Firms - DIAMOND, DOUGLAS W. (Journal of Finance, 1985)
ABSTRACT This paper provides a positive theory of voluntary disclosure by firms. Previous theoretical work on disclosure of new information by firms has demonstrated that releasing public information will often make all shareholders worse off, due to an adverse risk‐sharing effect. This paper uses a general equilibrium model with endogenous information collection to demonstrate that there exists a policy of disclosure of information which makes all shareholders better off than a policy of no disclosure. The welfare improvement occurs because of explicit information cost savings and improved risk sharing. This provides a positive theory of precommitment to disclosure, because it will be unanimously voted for by stockholders and will also represent the policy that will maximize value ex ante. In addition, it provides a “missing link” in financial signalling models. Apart from the effects on information production analyzed in this paper, most existing financial signalling models are inconsistent with a firm taking actions which facilitate future signalling because release of the signal makes all investors worse off.